Report of the 39th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2018)
Hội nghị lần thứ 39 của tổ chức liên nghị viện ASEAN được tổ chức tại Singapore từ ngày 3-7 tháng 9 năm 2018.